High-Speed Compressive Microscopy of Flowing Cells Using Sinusoidal Illumination Patterns - Qiang Guo; Hongwei Chen; Yuxi Wang; Yong Guo; Peng Liu; Xiurui Zhu; Zhen Cheng; Zhenming Yu; Sigang Yang; Minghua Chen; Shizhong Xie (IEEE Photonics Journal)
Single-pixel imaging (SPI) exploits the sparsity structure of natural images and enables image acquisition with far fewer measurements than the number of pixels. However, current SPI devices suffer from low imaging speed and an extremely time-consuming image reconstruction operation. Photonic time-stretch (PTS) technique is demonstrated to enable high-speed structured-illumination pattern generation, which significantly accelerates the imaging speed of conventional SPI devices. Meanwhile, to achieve fast image reconstruction, phase-shifted sinusoidal illumination patterns are used to acquire the Fourier spectrum of images and then a simple inverse fast Fourier transform (IFFT) operation is required for image reconstruction, which is quite computationally efficient. This paper presents a high-speed real-time compressive imaging system and its applications to imaging flow cytometry. Not only is a 625-kHz frame rate demonstrated, which is three orders of magnitude higher than that of a conventional SPI device, but the reconstruction process is remarkably accelerated as well, which enables our prototype system to operate in real time.